Patronage, punch-ups, and polite correspondence: the radical background of James Woodhouse’s early poetry - Bridgen, A (University of Pennsylvania Press (Penn Press), 2017)
In this essay, Adam Bridgen argues that the oft-condemned “sycophancy” of James Woodhouse’s early poetry is a misapprehension that overlooks the emergence of his evangelical, egalitarian beliefs in the mid-1760s. Reconsidering the letters between Woodhouse and his patrons reveals not only the influential friendships he cultivated as a plebeian poet but also the class prejudices he continued to encounter and resist, often forcefully. Although he conformed to a humble self-portrayal in his 1764 and 1766 Poems, Woodhouse’s subversion of praise allowed him to criticise as well as commend elite behaviour; viewing benevolence as a Christian duty faithful to the more equal society that God had intended, he praised patronage, in fact, for its levelling potential.